Iridium-catalyzed intramolecular [4 + 2] cycloadditions of alkynyl halides - Tigchelaar, Andrew; Tam, William (Beilstein Journal of Organic Chemistry, 2012)
Iridium-catalyzed intramolecular [4 + 2] cycloadditions of diene-tethered alkynyl halides were investigated by using [IrCl(cod)]2 as catalyst, and dppe was found to be the most suitable phosphine ligand for the reaction. No oxidative insertion of the iridium into the carbon–halide bond was observed, and the reactions proceeded to provide the halogenated cycloadducts in good yield (75–94%). These results are the first examples of cycloadditions of alkynyl halides using an iridium catalyst.
Keywords: alkynyl halide; cycloaddition; diene-tethered alkyne; iridium; transition-metal catalyst